2022
DOI: 10.1021/jacs.1c12463
|View full text |Cite
|
Sign up to set email alerts
|

Boryl Radical Activation of Benzylic C–OH Bond: Cross-Electrophile Coupling of Free Alcohols and CO2 via Photoredox Catalysis

Abstract: A new strategy for the direct cleavage of the C­(sp3)–OH bond has been developed via activation of free alcohols with neutral diphenyl boryl radical generated from sodium tetraphenylborate under mild visible light photoredox conditions. This strategy has been verified by cross-electrophile coupling of free alcohols and carbon dioxide for the synthesis of carboxylic acids. Direct transformation of a range of primary, secondary, and tertiary benzyl alcohols to acids has been achieved. Control experiments and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 143 publications
0
28
0
Order By: Relevance
“…Concurrently, Xia and co-workers reported a photoredox deoxycarboxylation method using boryl radicals as activators of free primary, secondary, and tertiary benzylic alcohols (Scheme 25). [40] Stern-Volmer quenching experiments revealed that tetraphenyl borate (NaBPh 4 ) was the species responsible for quenching the photocatalyst excited state via SET, forming the electron-deficient radical species 53, which was stabilised by the solvent DMF. Then, rapid coordination between the latter and benzylic alcohol promotes the cleavage of CÀ O bond and formation of the benzylic radical 51.…”
Section: Via Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, Xia and co-workers reported a photoredox deoxycarboxylation method using boryl radicals as activators of free primary, secondary, and tertiary benzylic alcohols (Scheme 25). [40] Stern-Volmer quenching experiments revealed that tetraphenyl borate (NaBPh 4 ) was the species responsible for quenching the photocatalyst excited state via SET, forming the electron-deficient radical species 53, which was stabilised by the solvent DMF. Then, rapid coordination between the latter and benzylic alcohol promotes the cleavage of CÀ O bond and formation of the benzylic radical 51.…”
Section: Via Photochemistrymentioning
confidence: 99%
“…The first study reported the synthesis of trisubstituted alkenes through an intermolecular alkylarylation of terminal alkynes with tertiary alkyl oxalates via photoredox/Ni dual catalysis (Scheme 21A). [36a] After a single-electron oxidation of the tertiary alkyl oxalate, the generated alkyl radical undergoes addition to the terminal alkyne, producing a linear alkenyl radical (40) in a regioselective manner. This high-energy radical is trapped by the Ni(0) species, eventually delivering the desired product.…”
Section: Via Photochemistrymentioning
confidence: 99%
“…Later, Xia's group developed a novel approach to activate the benzylic C–OH bond through the exploitation of a diphenyl boryl radical (Scheme 24). 37 This protocol also features mild conditions, good functional group compatibility and broad substrate scope, including primary, secondary, and tertiary benzyl alcohols. The reaction was carried out using the iridium complex as a photocatalyst, sodium tetraphenylborate (NaBPh 4 ) as the alcohol activation reagent, and quinuclidine as an additive to suppress the formation of reductive deoxygenation byproduct.…”
Section: Carboxylation Of C(sp3)–o Bondsmentioning
confidence: 99%
“…Progress in this field of cross-electrophile coupling has been achieved recently, usually based on the reaction of a halide electrophile with either a second halide electrophile or a nonhalide electrophile (Scheme a, path a). However, reductive cross-couplings using two nonhalide electrophiles as partners are underdeveloped and have rarely been studied (Scheme a, path b). Since Weix pioneered the cross-electrophile coupling reaction of aryl triflates with aryl tosylates by cleavage of two C–O bonds for C–C bond formation, the use of two oxygen-based electrophiles (oxo-electrophiles) as ecologically efficient counterparts to halides for developing deoxygenative cross-couplings has attracted considerable synthetic and mechanistic interest. The reductive coupling reaction between two oxo-electrophiles, for example orthogonal deoxygenative coupling of unactivated C–O electrophiles with unsaturated CO electrophiles by abstraction of hydrogen atoms, would be a valuable addition to forge C­(sp 2 )–C­(sp 3 ) bonds for enrichment of the synthetic toolbox toward important molecules, and remains an unsolved challenge (Scheme a, path c) …”
Section: Introductionmentioning
confidence: 99%